2009
DOI: 10.1029/2008ja013719
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationships among the South Atlantic Magnetic Anomaly, southern nighttime midlatitude trough, and nighttime Weddell Sea Anomaly during southern summer

Abstract: [1] This study utilized the multi-instrument data of the Defense Meteorological Satellite Program to investigate the evening/nighttime topside ionosphere during the 1996/1997 southern summer. A series of regional surface maps were constructed and permitted the tracking of the topside ionosphere's plasma density features, plasma composition, thermal structures, and vertical and horizontal plasma flows. These maps tracked a complete nighttime Weddell Sea Anomaly (WSA) and strong horizontal plasma flows that regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 65 publications
6
53
1
Order By: Relevance
“…Although the effects of dusk time EIA, south Atlantic magnetic anomaly, and the locations of the midlatitude ionospheric trough and the plasmapause in the formation of WSA are proposed in the past literature [ Horvath and Essex , 2003 and references therein], their relative importance in the formation/sustenance and variability of WSA is not well understood even today. A recent study shows that the heavy ion trough often coexists with the WSA, whereas the topside ionospheric signatures of the light‐ion trough show a close correspondence with the plasmapause location [ Horvath and Lovell , 2009]. The WSA is also seen to be affected by the electron density distributions in the low‐ to midlatitude sector [ Burns et al , 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of dusk time EIA, south Atlantic magnetic anomaly, and the locations of the midlatitude ionospheric trough and the plasmapause in the formation of WSA are proposed in the past literature [ Horvath and Essex , 2003 and references therein], their relative importance in the formation/sustenance and variability of WSA is not well understood even today. A recent study shows that the heavy ion trough often coexists with the WSA, whereas the topside ionospheric signatures of the light‐ion trough show a close correspondence with the plasmapause location [ Horvath and Lovell , 2009]. The WSA is also seen to be affected by the electron density distributions in the low‐ to midlatitude sector [ Burns et al , 2008].…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, that study provided observational evidence that the midlatitude heavy ion (Ni‐O + ) stagnation trough developed on its equatorward side and hence, the plasma at WSA latitudes was on convection paths. Furthermore, we also demonstrated that the plasmapause occurred on its poleward side during periods of increasing magnetic activity, and that the South Atlantic Magnetic Anomaly (SAMA) had a significant effect on both the trough and the nighttime WSA [ Horvath and Lovell , 2009a]. Also for the first time, this SAMA effect on the trough was modeled and the model reproduced the trough's poleward movement, instead of the usual equatorward movement, with increasing magnetic activity.…”
Section: Introductionmentioning
confidence: 85%
“…It contains the multiinstrument in situ plasma measurements of the DMSP‐F15 spacecraft that were collected at ∼850 km altitude along the ascending (northbound) passes. A detailed description of the DMSP orbit characteristics is given by Horvath [2006, 2007] and Horvath and Lovell [2009a, 2009b]. Along these F15 passes, the local time (LT) exhibited smaller variations between 75°N (geographic) and 75°S from 1900 LT through 2130 LT (at the equator) to midnight, respectively.…”
Section: Database Statistics and Methodsologymentioning
confidence: 99%
See 2 more Smart Citations